A Global k-means Approach for Autonomous Cluster Initialization of Probabilistic Neural Network - Chang, R.K.Y.; Loo, C.K.; Rao, M.V.C. (Informatica)
A Global k-means Approach for Autonomous Cluster Initialization of Probabilistic Neural Network